Response of heart rate variability and cardiorespiratory phase synchronization to routine bronchodilator test in patients with asthma - Chih-Hsiang Tsou; Lin-Sen Pon; Jun-Zhi Liang; Yun-Hsiang Chan; Kuan-Jung Chen; Feng-Shiang Cheng; Tsair Kao; Sai-Wei Yang (Chinese Journal of Physiology, 2021)
Heart rate variability (HRV) and cardiorespiratory phase synchronization (CRPS) were employed to study the cardio- and respiratory interactions in patients with asthma receiving inhalation of beta2-agonist (Berotec 200 mcg) for routine bronchodilator test. Both time- and frequency-domain parameters were used to analyze the HRV. A weighted G-index was introduced to study the quality of the CRPS. The HRV parameters, in both the time and frequency domains, exhibited significant changes pointing to a sympathetic activation of the autonomic balance immediately after the inhalation. On the other hand, the CRPS index barely changed throughout the entire process. This indicates that inhalation of beta2-agonist does not alter the CRPS appreciably, and that the CRPS, in contrast to HRV, is relatively stable in response to the inhalation of beta2-agonist in patients with asthma.